Axonal Guidance Signaling Pathway Is Suppressed in Human Nasal Polyps - Wu, Dawei; Mueller, Sarina K.; Nocera, Angela L.; Finn, Kristen; Libermann, Towia A.; Bleier, Benjamin S. (American Journal of Rhinology & Allergy, 2018)
Background Dysfunctional innervation might contribute to the pathogenesis of chronic rhinosinusitis with nasal polyps (CRSwNP), but the state of the axonal outgrowth signaling in CRSwNP is unknown. The purpose of this study was to explore the axonal outgrowth pathway-related protein expression in CRSwNP. Methods Institutional review board approved study in which tissue proteomes were compared between control and CRSwNP patients (n = 10/group) using an aptamer-based proteomic array and confirmed by whole transcriptomic analysis. Results Compared with controls, proteins associated with axonal guidance signaling pathway such as beta-nerve growth factor, semaphorin 3A, Ras-related C3 botulinum toxin substrate 1, Bcl-2, protein kinase C delta type, and Fyn were significantly decreased in patients with CRSwNP (fold change [FC] = -1.17, P = .002; FC = -1.09, P < .001; FC = -1.33, P < .001; FC = -1.31, P < .001; FC = -1.31, P = .004; and FC = -1.20, P = 0.012, respectively). In contrast, reticulon-4 receptor, an inhibitory factor, was significantly increased in patients with CRSwNP (FC = 1.25, P < .001). Furthermore, neuronal growth-associated proteins such as ciliary neurotrophic factor receptor subunit alpha, neuronal growth regulator 1, neuronal cell adhesion molecule, neural cell adhesion molecule L1, platelet-derived growth factor subunit A, and netrin-4 were all significantly decreased in patients with CRSwNP (FC = -1.25, P < .001; FC = -1.27, P = .002; FC = -1.65, P = .013; FC = -4.20, P < .001; FC = -1.28, P < .001; and FC = -2.31, P < .001, respectively). In contrast, tissue eosinophil count ( P < .001) and allergic inflammation factors such as IgE, periostin, and galectin-10 were all significantly increased in patients with CRSwNP (FC = 12.28, P < .001; FC = 3.95, P < .001; and FC = 2.44, P < .001, respectively). Furthermore, the log FC of the studied proteins expression significantly and positively correlated with log FC of their mRNA expression ( P < .001, r = .88). Conclusions Axonal guidance signaling and neural growth factors pathways proteins are significantly suppressed in eosinophilic CRSwNP.
EVALuna2:210634